Walking with intangibles: experiencing organisational learning. Issue 6 (9th June 2014) - Patterson, Jennifer
Abstract : Purpose: – The purpose of this paper is to apply experiential learning theory to discuss a UK project-based knowledge transfer partnership (KPT) project between a university and a third sector organisation offering outdoor and experiential education for around 32, 000 inner city children annually. It uses different models to critically consider how different experiential paradigms or world-views support different understandings of project experience in the real world. It examines the nature of experiential learning through project experience, applying a phenomenological inquiry to reflect on how experiential learning is valued academically and culturally. It considers environmental influences to balance the relational practices that represent intangible experiential elements in partnership work. Design/methodology/approach: – Using a postmodern qualitative methodology, this paper applies different frameworks to narrative, a synthesis of data from the project, an interview, literature and reflection to present a critical consideration of experiential learning constructs. It foregrounds the academic value of ethical subjectivity and as such also presents a reflective Feminist auto-ethnographic praxis grounded in the project. Findings: – Experiential learning is critical for human inquiry. Valuing experiential learning methods differently offers ethical applications for facilitating project work and partner relationships. Practical implications: – Applied experiential learning theory supports organisational understanding in project work. An ethics of subjectivity places equal value on expertise in its own environment leading to a facilitated rather than a hierarchical transfer of knowledge, critical for project success. The project is financially successful and has wide reaching social and environmental impact. Thinking differently about provision means a substantial number of children beyond those physically visiting the organisation will benefit through teacher training. Social implications: – The UK government no longer funds outdoor education. This paper demonstrates the importance of fostering environmental relationships for human identity, to support education for sustainable development and wider societal and environmental understandings. Originality/value: – Developed through project process this is a new values-based, environmental, organisational and educational transformational approach to partnership. It is useful in education, working in partnership with businesses and ESD.